Outdoor Recreation Physiological and Psychological Effects on Health - Nielsen, Hilde G. (IntechOpen, 2021)
Outdoor recreation refers to recreation/activity executed outdoors, most commonly in natural settings. At least in many high-income countries, outdoor recreation is by many considered as an attractive activity during spare time or holidays. People actively seek out activities such as walking in the mountains, climbing, hunting, horseback riding, skiing, etc., which are very often difficult to accommodate in ordinary working days. Some people find outdoor recreation attractive to the extent that they take several months or a year off from work in order to spend time in nature. Outdoor recreation stimulates a healthy lifestyle and increases public health, and it is important to develop outdoor activity habits from early childhood, a habit that should last for an entire lifetime. This book will take you through the definitions of outdoor recreation and different types of recreation. Furthermore, the book will also give you a snapshot of the physiological and psychological effects of outdoor recreation and why outdoor recreation is important for development in children and adolescents, and for adults and the older population, in addition to descriptions of some of the major and maybe the most used outdoor activities.